2022
DOI: 10.1155/2022/2451733
|View full text |Cite
|
Sign up to set email alerts
|

Carica papaya L. Leaves: Deciphering Its Antioxidant Bioactives, Biological Activities, Innovative Products, and Safety Aspects

Abstract: The prevalence of viral infections, cancer, and diabetes is increasing at an alarming rate around the world, and these diseases are now considered to be the most serious risks to human well-being in the modern period. There is a widespread practice in Asian countries of using papaya leaves (C. papaya L.) as herbal medicine, either alone or in combination with prescribed medications, to treat a variety of ailments. The importance of conducting the necessary descriptive studies in order to determine the safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 91 publications
2
13
0
3
Order By: Relevance
“…The phytochemical analysis of the ethanolic extract of C. papaya leaves (ECP) revealed the following bioactive compounds: flavonoids, tannins, phenolic compounds, saponins, glycosides, alkaloids, carbohydrates, quinones, phytosterols, triterpenoids, proteins, fixed oil, and fats (Table ). Previous studies suggested that C. papaya leaves have predominantly similar phytochemicals to different extracts. The present findings are consistent with the previous literature indicating that the ECP had similar bioactive compounds (Figure a,b). The total phenols and flavonoids in the ECP leaves were found to possess beneficial effects in an experimental model A previous study showed that the leaves of Physalis peruviana had promising potential effects on carbon tetrachloride induced nephrotoxicity in male albino rats.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The phytochemical analysis of the ethanolic extract of C. papaya leaves (ECP) revealed the following bioactive compounds: flavonoids, tannins, phenolic compounds, saponins, glycosides, alkaloids, carbohydrates, quinones, phytosterols, triterpenoids, proteins, fixed oil, and fats (Table ). Previous studies suggested that C. papaya leaves have predominantly similar phytochemicals to different extracts. The present findings are consistent with the previous literature indicating that the ECP had similar bioactive compounds (Figure a,b). The total phenols and flavonoids in the ECP leaves were found to possess beneficial effects in an experimental model A previous study showed that the leaves of Physalis peruviana had promising potential effects on carbon tetrachloride induced nephrotoxicity in male albino rats.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies suggested that C. papaya leaves have predominantly similar phytochemicals to different extracts. 39 41 The present findings are consistent with the previous literature indicating that the ECP had similar bioactive compounds ( Figure 2 a,b). The total phenols and flavonoids in the ECP leaves were found to possess beneficial effects in an experimental model A previous study showed that the leaves of Physalis peruviana had promising potential effects on carbon tetrachloride induced nephrotoxicity in male albino rats.…”
Section: Resultssupporting
confidence: 93%
“…As a result, the search for these nephroprotective compounds has grown. Carica papaya seeds have long been utilized in diverse civilizations for their therapeutic attributes, effectively treating a wide range of health conditions, including digestive disorders and parasite infections [4]. Scientific inquiry into these seeds has unveiled a rich phytochemical landscape, teeming with bioactive compounds such as flavonoids, alkaloids, and saponins.…”
Section: Introductionmentioning
confidence: 99%
“…( Aruljothi et al, 2014 ). According to many studies, papaya’s fruits are a potent source of antibacterial agents that can be used by pharmaceutical industries to produce medications ( Hariono et al, 2021 ; Sharma et al, 2022 ). Additionally, researchers in China found that papaya seed essential oil (EO) has promising anticandidal activity and identified C. papaya as a potential natural source of antifungal agents ( He et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%